Negative life events, resilience, and depression among low income drug addict wives in Malaysia - Ahmad Shahril, Nurul Saidatus Shaja’ah; Arshat, Zarinah; Adnan, Haikal Anuar; Ismail, Nellie; Ahmad, Sa’odah (Human Resources Management Academic Research Society (HRMARS), 2024)
There are growing studies on depression among women in the general population. While empirical works circulating stressful experiences among women with drug-addicted husbands have been conducted, little published research centred their interest, particularly on the associated factors of depression among women who face drug addiction issues of their husbands. Thus, the present study was conducted as an attempt to examine the association between their experienced negative life events, resilience, and depression. Employing a purposive sampling method, a total of 132 wives of drug addicts were recruited to participate in this study. Data were collected from six states in Malaysia using a structured questionnaire consisting Negative Event (Hassles) Scale (NES), Brief Resilience Scale (BRS), and Zung’s Self-Rating Depression Scale (SDS). Statistical Package of Social Science (SPSS) software version 22 was used to analyse the data collected. Inferential analysis revealed that negative life events, resilience, and depression demonstrated significant relationships respectively. Specifically, negative life events was found correlated to depression. Whereas, a negative correlation was identified between resilience and depression. Thus, both negative life events and resilience are evidenced to have an impact on depression among wives of drug addicts in this study. The present study offers supplemental strategies to drug addict wives, advocates, academicians, practitioners, and policymakers in order to address depression issues in this community through empowering stress management and resilience to reduce the risk of depression.